DULAMAYO VILLAGE FROM 1941 TO 1999 - Usman, Intan; Mohammad, Sutrisno; Hasan, Renol (CV. Fahr Publishing, 2025)
This research aims to examine the history of the establishment of Dulamayo Village between 1941 and 1999, as well as its subsequent development. The method employed in this study is the historical method, which consists of four stages: heuristics (source collection), source verification or criticism—encompassing both external and internal criticism—interpretation, and historiography (historical writing). The findings reveal that Dulamayo Village was established in 1941 in Bongomeme District, approximately 25 kilometers from Gorontalo City. Prior to that, during the 17th and 18th centuries, Bongomeme was still a small hamlet that gradually developed into a larger district, eventually leading to territorial expansion that gave birth to Dulamayo Village. The name “Dulamayo” originated from an area where large wild mango trees grew abundantly, producing plentiful fruit; thus, since the mid-18th century, the area became known as Kampung Dulamayo. In the 19th century, this region was incorporated into Batudaa District before eventually becoming part of Bongomeme District. The period between 1941 and 1999 reflects significant development: in the early years, there were no schools, the community relied solely on subsistence farming, and the population remained small. However, by 1999, formal educational institutions had been established, agricultural products were being traded in markets, and the population increased substantially due to migration. Nevertheless, the tradition of Huhuyula, or mutual cooperation, continued to be preserved as a vital cultural identity of the community.